Pengaruh Variasi Beban Latihan Terhadap Peningkatan Power Lengan Siswa Ekstrakurikuler Bola Voli - Oktavianus, Muhamad Rizki; Risma, Risma; Ropi, Ucu Abdul; Nursasih, Isna Daniyati (Jurnal Keolahragaan, 2026)
ABSTRACT This study was conducted to examine the extent to which variations in training load affect the arm strength of students participating in volleyball extracurricular activities at SMA Negeri 3 Ciamis. Until now, physical training at the school has not specifically focused on strengthening arm muscles, even though adolescence is an ideal period for physical development. The method used was a quasi-experimental design with a one-group pretest-posttest setup, involving 20 students. They underwent regular dumbbell training with varying weights ranging from 3 kg to 6 kg over a certain period. Arm strength was measured using the Two-Hand Medicine Ball Throw test before and after the training. The results showed a significant improvement, proving that variations in training load are highly effective in strengthening the arms and enhancing technical skills such as serving and smashing. Additionally, varied training helped maintain student enthusiasm and motivation. The study recommends that coaches and physical education teachers implement more structured and diverse training programs. For future research, it is suggested to involve a control group and consider other factors such as gender and experience to obtain more comprehensive results.,Penelitian ini dilakukan untuk melihat seberapa besar pengaruh variasi beban latihan terhadap kekuatan lengan siswa yang mengikuti ekstrakurikuler bola voli di SMA Negeri 3 Ciamis. Selama ini, latihan fisik di sekolah tersebut belum fokus pada penguatan otot lengan, padahal masa remaja adalah waktu yang tepat untuk mengembangkan fisik. Metode yang digunakan adalah quasi eksperimen dengan desain pretest-posttest satu kelompok, melibatkan 20 siswa. Mereka menjalani latihan dumbbell dengan beban yang bervariasi, mulai dari 3 kg hingga 6 kg, secara rutin selama beberapa waktu. Kekuatan lengan diukur dengan tes Two Hand Medicine Ball Throw sebelum dan sesudah latihan. Hasilnya menunjukkan peningkatan yang signifikan, yang membuktikan bahwa variasi beban latihan sangat efektif untuk memperkuat lengan sekaligus meningkatkan kemampuan teknik seperti servis dan smash. Selain itu, latihan yang bervariasi juga membantu menjaga semangat dan motivasi siswa. Penelitian ini menyarankan agar pelatih dan guru olahraga menerapkan program latihan yang lebih terencana dan beragam. Untuk penelitian berikutnya, disarankan melibatkan kelompok kontrol dan mempertimbangkan faktor lain seperti jenis kelamin dan pengalaman agar hasilnya lebih lengkap.